Exploring an adapted Risk Behaviour Diagnosis Scale among Indigenous Australian women who had experiences of smoking during pregnancy: a cross-sectional survey in regional New South Wales, Australia. Issue 5 (30th May 2017) - Gould, Gillian Sandra; Bovill, Michelle; Chiu, Simon; Bonevski, Billie; Oldmeadow, Christopher
Abstract : Objectives: Explore Aboriginal women's responses to an adapted Risk Behaviour Diagnosis (RBD) Scale about smoking in pregnancy. Methods and design: An Aboriginal researcher interviewed women and completed a cross-sectional survey including 20 Likert scales. Setting: Aboriginal Community Controlled Health Services, community groups and playgroups and Aboriginal Maternity Services in regional New South Wales, Australia. Participants: Aboriginal women (n=20) who were pregnant or gave birth in the preceding 18 months; included if they had experiences of smoking or quitting during pregnancy. Primary and secondary outcome measures: Primary outcomes: RBD constructs of perceived threat and perceived efficacy, dichotomised into high versus low. Women who had quit smoking, answered retrospectively. Secondary outcome measures: smoking status, intentions to quit smoking (danger control), protection responses (to babies/others) and fear control responses (denial/refutation). Scales were assessed for internal consistency. A chart plotted responses from low to high efficacy and low to high threat. Results: RBD Scales had moderate-to-good consistency (0.67–0.89 Cronbach's alpha). Nine women had quit and 11 were smoking; 6 currently pregnant and 14 recently pregnant. Mean efficacy level 3.9 (SD=0.7); mean threat 4.3 (SD=0.7). On inspection, a scatter plot revealed a cluster of 12 women in the high efficacy-high threat quadrant—of these 11 had quit or had a high intention of quitting. Conversely, a group with low threat-low efficacy (5 women) were all smokers and had high fear control responses: of these, 4 had low protection responses. Pregnant women had a non-significant trend for higher threat and lower efficacy, than those previously pregnant. Conclusion: Findings were consistent with a previously validated RBD Scale showing Aboriginal smokers with high efficacy-high threat had greater intentions to quit smoking. The RBD Scale could have diagnostic potential to tailor health messages. Longitudinal research required with a larger sample to explore associations with the RBD Scale and quitting.